REPRODUCTIVE BIOLOGY OF AELUROPUS LilTORALiS (Willd.) Parl. - Pollak, G; Waisel, Y (Annals of Arid Zone, 2016)
Germination and. vegetative reproduction in Aeluropua litoralis (Willd.) Parl. was investigated under various environmental conditions. Germination of caryopses is light-dependent. Temperature affects both germination percentage and germination rates. Although Aeluropus litoralis is a halophytic species, optimal germination occurs in non-saline media. Practically no germination was found in media containing NaCl in concentrations exceeding O.3M. Vegetative reproduction is more tolerant to NaCl than reproduction from seeds; cuttings root even in media containing O.6M NaCl.